1994
DOI: 10.1016/s0010-9452(13)80322-x
|View full text |Cite
|
Sign up to set email alerts
|

Are Semantic Systems Separately Represented in the Brain? The Case of Living Category Impairment

Abstract: Following herpes encephalitis, a patient showed impaired knowledge of animals, fruits and vegetables, flowers and food (so called living things categories), whatever the modality in which stimuli were presented and responses were given. A series of experiments showed that the deficit specifically affected the ability to retrieve the perceptual features of the living stimuli defining their shape, while knowledge of their functional-encyclopedic properties was preserved. The patient had no problems with man-made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(94 citation statements)
references
References 31 publications
3
87
0
1
Order By: Relevance
“…Unfortunately our materials were not designed to allow systematic comparisons among relevant types of perceptual property for SE. Our data also impose further constraints on the details of a distributed account, over and above those suggested by De Renzi and Lucchelli (1994). Specifically, the inter-relations among visual and non-visual properties must allow the visual properties of non-living things to be activated rapidly and automatically, such that they can support normal on-line priming in situations where controlled inference processes cannot operate.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Unfortunately our materials were not designed to allow systematic comparisons among relevant types of perceptual property for SE. Our data also impose further constraints on the details of a distributed account, over and above those suggested by De Renzi and Lucchelli (1994). Specifically, the inter-relations among visual and non-visual properties must allow the visual properties of non-living things to be activated rapidly and automatically, such that they can support normal on-line priming in situations where controlled inference processes cannot operate.…”
Section: Discussionmentioning
confidence: 71%
“…This hypothesis has gained support from several studies of patients with category-specific deficits for living things, who have all demonstrated the predicted pattern of a greater problem for visual than nonvisual semantic properties (De Renzi & Lucchelli, 1994;Farah, Hammond, Mehta & Ratcliff, 1989;Hart & Gordon, 1992;Sartori & Job, 1988;Sartori et al, 1993a;Sartori, Job, Miozzo, Zago, & Marchiori, 1993b;Silveri & Gainotti, 1988). There is also converging evidence from studies of unimpaired subjects that visual/perceptual properties are particularly important for the identification of living things (e.g.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Several cases of category-specific deficit for biological things also displayed an important impairment in drawing affected category exemplars from memory (e.g., De Renzi & Lucchelli, 1994;Forde et al, 1997;Sartori & Job, 1988;Sheridan & Humphreys, 1993). Two such tests were presented to ER: memory-drawing and drawing completion.…”
Section: Cognitive Neuropsychology 2002 19 (4) Kolinsky Et Almentioning
confidence: 99%
“…However, the expression category-specific semantic impairment for living things must be considered as a shorthand "as not all the affected categories are living and not all living categories are affected" (Gainotti, Silveri, Daniele, & Giustolisi, 1995, p. 256). In fact, several studies have shown that in patients with a category-specific impairment for living things, food and, sometimes, musical instruments are also impaired, whereas body parts are often spared (e.g., Basso et al, 1988;De Renzi & Lucchelli, 1994;Forde et al, 1997;Sartori & Job, 1988;Sheridan & Humphreys, 1993;Silveri & Gainotti, 1988;Sirigu et al, 1991;Warrington & Shallice, 1984).…”
Section: Inter-category Variabilitymentioning
confidence: 99%